Excavation on Nimowa Island, Louisiade Archipelago, Papua New Guinea: Insights Into Cultural Practices and the Development of Exchange Networks in the Southern Massim Region. (3rd July 2017) - Shaw, Ben; Dickinson, William R.
ABSTRACT: Small-scale excavation was undertaken at the Malakai site on the small island of Nimowa, located in the Louisiade Archipelago, Massim region, Papua New Guinea. This is the first excavation to be reported in detail from the archipelago, with the Malakai site providing insight into cultural practices on the island and pottery exchange in the southern Massim region. A stratified deposit was revealed with dense cultural material, first inhabited from 1350 to 1290 cal. BP, with a subsequent period of settlement within the last 460–300 cal. years. Pottery, shell, and stone artifacts were recovered, as well as human skeletal remains in a primary burial context, which contributes to understanding regional patterns of prehistoric mortuary activity. It is argued that Nimowa was already part of an exchange network that encompassed many of the southern Massim islands when the Malakai site was first occupied. There is increased diversity in the number of vessel forms in later prehistory, but with remarkable continuity in the decorative motifs over time, suggesting some degree of regional social cohesion in the southern Massim. It appears that the northern Massim islands were not a major supplier of pottery to Nimowa. The implications for the prehistory of the wider region are subsequently discussed.